The randomised prospective comparative study to see the duration of analgesia following intravenous or rectal acetaminophen after adenotonsillectomy in children - Gupta, Neerupam; Bhadrala, Naine; ., Jasmeen; ., Saloni (International Journal of Contemporary Pediatrics, 2019)
Background: The greatest advance in pediatric pain medicine is the recognition that untreated pain is a significant cause of morbidity and even mortality after surgical trauma. Author compared the analgesic efficacy and duration of analgesia of rectal acetaminophen and I.V. acetaminophen. Methods: A total of 80 children in the age group of 2-5 years were randomly selected and divided into 2 groups. Group I received 15 mg/kg I.V. paracetamol and group II received 40 mg/kg rectal acetaminophen. Post-operative pain scores were measured using Face, Legs, Activity, Cry and Consolability scale and duration of analgesia were recorded and compared. Results: The pain scores in group I was lower immediately after extubation and at 30 minutes post extubations but at one, two and four hours the pains score were comparable in both the groups. At 6 hours, the pain score was significantly more in I.V. group and also the duration of analgesia was 9-10 hours in rectal acetaminophen group where as in I.V. group, it was 5-6 hours. Conclusions: Rectal acetaminophen 40 mg/kg produces prolonged analgesia as compared to I.V. paracetamol 15 mg/kg and also is more convenient and cost effective and is devoid of side effects of I.V. cannulation.